Making Love Just : Sexual Ethics for Perplexing times - Ellison, Marvin Mahan (Book collections on Project MUSE., 2012)
Ethical reflection about sexuality is increasingly controversial, complex, and conflicted. After centuries of conflicting messages from the tradition, Christians are understandably confused about how exactly the good news pertains to sexuality. Using a series of provocative questions, Marvin Ellison, a pioneer in contemporary Christian rethinking of sexuality and sexual ethics, attempts to increase readers' skills and confidence for engaging in ethical deliberation about sexuality. Redrawing the conventional, rule-based sexual morality, often rigidly and legalistically applied or broadly ignor.